Determinants of entrepreneurial behaviour in FATA Pakistan - Muhammad, Ali; Junaid, Muhammad (International Food Policy Research Institute, 2016)
This research investigates determinants of entrepreneurial behaviour in one of the most impoverished areas of Paki-stan, the Federally Administered Tribal Areas (FATA). Unlike the developed world, the scenario in emerging econo-mies is quite different, where entrepreneurs have to rely primarily on socio-cultural factors that facilitate them to pursue entrepreneurship as a means to earn livelihoods. However, little predictive empirical work has investigated enterprising behaviour in the tribal areas of Pakistan. This study examines the relative strength of selected entrepre-neurial determinant in the Pashtun tribal culture. Persistent wars, economic downturn, and strong cultural adherence have turned the Pashtun tribesmen into necessity entrepreneurs. Based on primary data from 462 respondents, entre-preneurial behaviour measured by self-reported views toward risk-taking and innovativeness are related to economic, institutional, and cultural constructs using logistic regression models. Different sets of predictors emerged for risk-taking and innovativeness. We find some, but limited support for hypothesized determinants of entrepreneurial be-havior. This study informs academics as to how entrepreneurial behaviour of Pashtuns can be enhanced, setting up hypotheses and results for future research exploration, and can guide policy to stimulate underlying factors that will promote entrepreneurship in FATA.